Prevalence and risk factors of adult attention deficit hyperactivity disorder in university students: A study from the United Arab Emirates - Salama, Rasha A.; Tadross, Talaat M.; Ammar, Ali R.; Manasrah, Haya T.; Razack, Rishana A.; Koya, Shameena M.; Wadid, Nihal A.; Patni, Mohamed AF.; Khan, Shehla S. (Narra J, 2025)
Attention deficit hyperactivity disorder (ADHD), once considered primarily a childhood condition, is now increasingly recognized as a disorder that persists into adulthood and significantly impacts academic and professional success. The aim of this study was to investigate the prevalence of ADHD and identify associated risk factors among university students. A cross-sectional study was conducted over a period of six months at Ras Al Khaimah Medical and Health Sciences University, United Arab Emirates. Data were collected through a self-report questionnaire addressing sociodemographic, lifestyle, and family environment factors. ADHD symptoms were assessed using the World Health Organization Adult ADHD Self-Report Scale version 1.1, based on the Diagnostic and Statistical Manual of Mental Disorders - Fifth Edition criteria. The study sample included 472 students, with a mean age of 19.9±1.85 years. The overall prevalence of ADHD was 13.6% (n=64). Logistic regression analysis revealed significant associations between the mother's smoking status (odds ratio (OR): 2.35; 95% confidence interval (95%CI): 1.949–5.862, p=0.050) and living in shared housing (OR: 3.35; 95%CI: 1.674–6.723, p=0.001) with increased odds of ADHD. Conversely, being male (OR: 0.4; 95%CI: 0.216–0.891, p=0.02) and being born full-term (OR: 0.331; 95%CI: 0.138–0.794, p=0.013) were associated with decreased odds of ADHD. Other factors, such as college affiliation, smoking status, exercise habits, maternal employment, mode of delivery, and pregnancy complications, were not significant risk factors. These findings highlight the need for targeted interventions in university settings, including early screening, tailored support services, and increased staff awareness, to support students with ADHD and enhance their academic success and well-being.